A cis‐regulatory change underlying the motor neuron‐specific loss of Ebf expression in immotile tunicate larvae. Issue 2 (23rd December 2020) - Lowe, Elijah K.; Racioppi, Claudia; Peyriéras, Nadine; Ristoratore, Filomena; Christiaen, Lionel; Swalla, Billie J.; Stolfi, Alberto
Abstract: Many species in the tunicate family Molgulidae have independently lost their swimming larval form and instead develop as tailless, immotile larvae. These larvae do not develop structures that are essential for swimming such as the notochord, otolith, and tail muscles. However, little is known about neural development in these nonswimming larvae. Here, we studied the patterning of the Motor Ganglion (MG) of Molgula occulta, a nonswimming species. We found that spatial patterns of MG neuron regulators in this species are conserved, compared with species with swimming larvae, suggesting that the gene networks regulating their expression are intact despite the loss of swimming. However, expression of the key motor neuron regulatory gene Ebf (Collier/Olf/EBF) was reduced in the developing MG of M. occulta when compared with molgulid species with swimming larvae. This was corroborated by measuring allele‐specific expression of Ebf in hybrid embryos from crosses of M. occulta with the swimming species M. oculata . Heterologous reporter construct assays in the model tunicate species Ciona robusta revealed a specific cis ‐regulatory sequence change that reduces expression of Ebf in the MG, but not in other cells. Taken together, these data suggest that MG neurons are still specified in M. occulta larvae, but their differentiation might be impaired due to reduction of Ebf expression levels. Abstract : Research highlights: We report the larval motor neuron‐specific loss of expression of the transcription factor‐encoding gene, Ebf, in the tunicate Molgula occulta, which has undergone evolutionary loss of the swimming larval life cycle stage. We identified cis ‐regulatory sequence differences between M. occulta and the closely related M. oculata, which has retained the swimming larval stage, that likely affect the transcription of Ebf specifically in larval motor neurons, but not other neurons or tissues.